PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP INTENTION TO QUIT DIMEDIASI OLEH KEPUASAN KERJA PADA KARYAWAN - Prasetya, Putu Wahyu Yana; Dewi, I Gusti Ayu Manuati (E-Jurnal Manajemen; Vol 8 No 4 (2019), 2019)
The research aims to examine the effect of transformational leadership style on intention to quit mediated by job satisfaction. This research was conducted on employees at PT. Visionet Data Internasional Service Point Denpasar, Bali. The population contained in this study were 48 and by using saturated samples there were 48 respondents. The method of data collection is done by questionnaire. Data analysis techniques used are Factor Analysis, Classical Assumption Test and Path Analysis. The results showed that transformational leadership style variables had no negative and significant effect on intention to quit, transformational leadership style had a positive and significant effect on job satisfaction, job satisfaction had a negative and significant effect on intention to quit, job satisfaction had a mediating role in a negative and significant influence transformational leadership style towards intention to quit So the higher the transformational leadership style and job satisfaction in the company will be able to reduce the level of intention to quit employees. Keywords: transformational leadership style, job satisfaction, intention to quit